Remembrance Perak unsung hero in visual approaches by using contemporary pedagogy / Nur Kyairina Ridwana Putri Rizdwan and Mohd Khairul Azahari Abdul Rani - Rizdwan, Nur Kyairina Ridwana Putri; Abdul Rani, Mohd Khairul Azahari (2018)
Unsung Hero is about heroic figure that has not been recognized and acknowledged by the public of their contributions and sacrifices for our country's history. This paper will highlight Sybil Kathigasu as the Unsung Hero that the society need to know. She was a wife to Dr Abdon Clement Kathigasu and also a nurse working with her husband. The tragedy happened after the couple helped guerrillas hiding in the Malayan jungles. She had successfully help hundreds of people, before she was arrested. The main objective of this paper is to introduce her story as a historical material by using pedagogy technical to attract student's interest in history subject. For this research, the methods used are, qualitative and quantitative methods. These two methods were appropriate and relevant to be incorporated in this study as a data collection process. Therefore, researcher found that by using visual language it will be easier to attract people/readers especially the new generation to appreciate her story. Based on this study, the story of heroism we have not seen, the unknown sacrifice and the services provided will help the community to learn about the forgotten of Florence Nightingale Malaysia.